Alguns adjuntos temporais com especial relevância para a tradução inglês-português: o caso de since-desde e expressões afins - Móia, Telmo (Revista da Associação Portuguesa de Linguística, 2021)
This paper addresses the semantic analysis of polyvalent temporal adjuncts headed by (mainly) English since and Portuguese desde, and problems in translation from English to Portuguese. Four semantic values of the single operator since are considered (the second and fourth of which are not normally considered autonomously in the English literature) – durative location, derived durative location (in association with adjunct-triggered Aktionsart shift), simple inclusive location and temporal circumscription of quantification. Furthermore, the typically monovalent phrase ever since and the bivalent phrase long since are also taken into account. The fact the Portuguese desde – contrary to English since – is not normally associated with simple inclusive locations is the source of many translation problems. Other interesting grammatical issues, involving long since, are also addressed. The translation data is obtained from the website linguee.com (where six different types of problems are found), and the semantic analysis is made with the logic of the Discourse Representation Theory, elaborating on my previous work, Móia (2000).